Study on the spatio-temporal dynamics of forest carbon sources and sinks in Xinjiang based on process models and their climate response mechanisms - Zhou, Jia; Zan, Mei; Zhai, Lili; Ke, Jian; Zhao, Zhongqiong (Frontiers in Forests and Global Change, 2025)
Net Ecosystem Productivity (NEP) serves as a critical metric for evaluating the carbon sequestration capability of forest ecosystems. As a vast territory forming a vital ecological shield in northern China, Xinjiang possesses notably complex and varied forest environments, making an assessment of its ecosystem carbon cycle's spatial patterns and climatic responses highly significant. This study employed the Integrated Terrestrial Ecosystem Carbon-budget (InTEC) model, driven by multi-source remote sensing and reanalysis datasets for meteorology, vegetation, soil, and topography, to simulate the spatiotemporal dynamics of Xinjiang's forest NEP from 1901 to 2060. Using trend and partial correlation analyses, this study examined the spatiotemporal evolution of forest NEP and its response to changing climatic factors under three representative concentration pathways from the Coupled Model Intercomparison Project Phase 6 (CMIP6): SSP126, SSP245, and SSP585. The results indicate that: (1) For the 1901-2022 period, the average forest NEP in Xinjiang was 47.81 g C·m−2·yr−1, demonstrating a fluctuating upward trend at an average rate of 0.52 g C·m−2·yr−1. The overall spatial pattern showed higher values in the east and north compared to the west and south. (2) The carbon fixation potential of Xinjiang's forests under the SSP126 scenario is projected to be considerably higher than under other scenarios. The mean annual NEP values for 2023-2060 are estimated to be 122.88, 114.28, and 108.54 g C·m−2·yr−1 for the three respective scenarios. While NEP is expected to increase with fluctuations until around 2035 in all pathways, a decline may occur after 2045 under high-emission scenarios, potentially due to elevated temperatures, drought, frequent extreme events, and substantial increases in nitrogen deposition. This decrease is anticipated to be concentrated in the piedmont plains of the Tianshan Mountains and the areas surrounding the Tarim Basin. (3) The positive control of precipitation on Xinjiang's forest NEP is stronger than that of temperature. The partial correlation between temperature and NEP shows significant geographical differentiation, being positive in cool, humid montane forests and negative in hot, arid regions. Solar radiation and vapor pressure exhibit a distinct positive relationship with forest NEP, affecting 76.23% and 63.83% of the study area, respectively. These findings reveal the centennial-scale spatiotemporal dynamics of forest NEP in Xinjiang and its future carbon uptake potential, providing a valuable reference for assessing the region's carbon sequestration capacity.